A dual‐feed MIMO antenna pair with one shared radiator and two isolated ports for fifth generation mobile communication band. Issue 9 (11th July 2017) - Chen, Aobo; Zhang, Jianqiang; Zhao, Luyu; Yin, Yingzeng
Abstract: In this article, a pair of unsymmetrical dual‐feed antennas with one shared radiator and two isolated ports is proposed for multiple‐input‐multiple‐output (MIMO) systems. The proposed antenna pair achieves high isolation between the two ports by properly adjusting the distance between the two feeding ports and the position and length of shorting strips on the radiator. The antenna has simple structure and covers the 3.3‐3.7 GHz band, which could meet the demand of future 5G applications. The measured results show that antenna has good impedance matching (better than 10 dB return loss) and high port isolation (better than 20 dB isolation) from 3.35 to 3.65 GHz. The total efficiencies are above 55% and the envelope correlation coefficient is <0.1, which is sufficient for MIMO applications.